Evidence of fish following towed oil and gas platforms to a reefing site and rapid colonisation. (September 2022) - Marnane, Michael J.; Schramm, Karl D.; Driessen, Damon; Fullwood, Laura A.; Saunders, Benjamin J.; Songploy, Se; Kettratad, Jes; Sitaworawet, Paweena; Chaiyakul, Sarin; Chankong, Anchalee; Chantarawat, Nararat; Elsdon, Travis S.; et al.
Abstract: We investigated the composition and abundance of fish assemblages associated with seven offshore oil and gas platform jackets in the Gulf of Thailand before (pre-lift and pre-tow), and immediately after relocation (post-tow and reefed). Jackets were cut, lifted until partly out of the water, and attached to the rear of a heavy lift vessel. They were towed at speeds of 2.7 – 3.3 knots for between 133.9 and 205.4 km before being placed on the seafloor at an artificial reef site. Sixteen species of fish were observed both before and after jacket towing. We believe these species have sought refuge in the complex structures out of the current and have remained with the jackets. Ten species of fish were observed before towing, but not after. A further seven species of fish were only observed after the jackets were relocated onto the seafloor and were assumed to be early colonisers to the structures. The paper provides empirical evidence of a much-discussed paradigm that fish can swim great distances following moved structures, and further evidence of the ability of fish to rapidly colonise reefed structures. Graphical abstract: Image 1 Highlights: Fish on oil and gas jackets were surveyed before, during and after towing. 16 species of fish remained with the jackets during relocation (followers). 10 species of fish did not follow the jackets (deserters). 7 new species of fish were observed (colonisers) within two days of placement of jackets on the seabed. "Followers" likely sought refuge in the complex structures out of the current during towing.